Modeling the dispersion of endocrine disruptors in the Santos Estuarine System (Sao Paulo State, Brazil) - Gimiliani, Giovana Teixeira [UNESP]; Carelli Fontes, Roberto Fioravanti [UNESP]; Souza Abessa, Denis Moledo de [UNESP] (Inst Oceanografico, Univ Sao Paulo, 2016)
Estrogens are hormones responsible for growth and reproduction. They are naturally synthesized by animals and humans alike. Xenoestrogens are identical to natural hormones, but they are man-made and used as oral contraceptives. Xenoestrogens are a specific group of drugs found in domestic wastewater and some environmental matrices. These compounds remain after conventional sewage treatment and, consequently, affect both the environment and non-target aquatic organisms. In this study, we used the Delft3D hydrodynamic model to estimate the amount of both natural and synthetic estrogens that have been released in the Estuarine System of Santos and Sao Vicente and the Santos Bay. The data on flow from the sewage treatment plants and on average concentrations of natural and synthetic estrogens released in aquatic environments were obtained from the literature. The results of the modeling showed higher concentrations of estrogens in the estuarine waters of the Largo Pompeba region, the Sao Vicente Canal, and the Santos Bay, which are regions that receive greater inflows of domestic sewage. The results also suggest that higher concentrations of estrogenic compounds are expected to be found in areas with higher levels of salinity.
Keywords: Estrogens; Dispersion; Delft 3; Santos Estuarine System; Santos Bay